The Effect of Whole-Body Vibration on Proprioception and Motor Function for Individuals with Moderate Parkinson Disease: A Single-Blind Randomized Controlled Trial - Kuan-yi Li; Yu-ju Cho; Rou-shayn Chen (Occupational Therapy International)
Introduction. Previous studies have shown that whole-body vibration (WBV) may have a potential impact on gait and balance in individuals with Parkinson’s disease (PD). However, this body of work has proven inconclusive due to the diverse disease progression and broad age range associated with PD. The effects of WBV on proprioception, a sense frequently affected by PD, has rarely been studied. Objective. To investigate the short-term effect of WBV on proprioception and motor function for individual with moderate PD. Design. A single-blind randomized controlled trial. Setting. A hospital and a laboratory. Participants. 32 participants with moderate PD were recruited and randomly assigned into either the WBV or conventional therapy groups. Interventions. For the WBV group, each treatment session included five, one-minute bouts of whole-body vibration paired with one-minute rest (frequency: 6 Hz; amplitude: 3 mm). Each conventional therapy participant received balance and mobility training for 10 minutes. Main Outcome Measures. Outcome measures included proprioceptive sensitivity of the upper limb, position sense of the knee joint, Unified Parkinson’s disease rating scale : motor section (UPDRS-motor), functional reach test (FRT), and the timed up and go test (TUG). Results. No statistically significant difference was found between groups. However, both groups showed a significant improvement in motor function after treatment, including UPDRS-motor (P=0.04), less affected side of FRT (P=0.019), and TUG (P=0.006). Conclusions. Although the effect of WBV was not superior to the conventional therapy, it provided a passive and safe clinical intervention as an alternative treatment, especially for individuals with motor impairment or poor balance function.